Following [videorecording (DVD)] - Nolan, Christopher, 1970-; Nolan, Christopher, 1970-; Nolan, Christopher, 1970-; Nolan, Christopher, 1970-; Nolan, Christopher, 1970-; Haw, Alex; Theobald, Jeremy; Theobald, Jeremy; Russell, Lucy, 1972-; Nolan, John, 1938- (Criterion collection, 2012)
Is the fragmented tale of an unemployed young writer who trails strangers through London, hoping that they will provide inspiration for his first novel. He gets more than he bargained for with one of his unwitting subjects, who leads him down a dark, criminal path. Special features included.